액체식 직접 접촉 냉각장치의 노즐배열 최적화：정풍량 해석 - 김원년; 김서영 (대한설비공학회, 2006)
For the design of a liquid direct contact cooling system, thermal and hydraulic analysis has been carried out. Well-known Zukauskas correlations are used to estimate the Nusselt number between the liquid refrigerant columns and the inlet airflow. The inlet air velocity is set at a typical value used in an actual showcase. For a constant column number, the best nozzle arrangement is determined for the maximum heat transfer. Heat transfer increases as the transverse pitch of the refrigerant column decreases. Among all the cases dealt with in the present study, the staggered arrangement with 140-columns of 14×10 shows the best thermal performance and the expected temperature drop is 27.8℃. The effect of downstream refrigerant columns on the overall thermal performance is investigated as well.